2022
DOI: 10.3389/fphys.2022.822098
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch Responses Evoked by Sound Pattern Violation in the Songbird Forebrain Suggest Common Auditory Processing With Human

Abstract: Learning sound patterns in the natural auditory scene and detecting deviant patterns are adaptive behaviors that aid animals in predicting future events and behaving accordingly. Mismatch negativity (MMN) is a component of the event-related potential (ERP) that is reported in humans when they are exposed to unexpected or rare stimuli. MMN has been studied in several non-human animals using an oddball task by presenting deviant pure tones that were interspersed within a sequence of standard pure tones and compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
(94 reference statements)
0
2
0
Order By: Relevance
“…Studies in rodents and pigeons successfully identified responses meeting these criteria 14,15,18 . However, efforts to identify an equivalent of MMN in songbirds and frogs failed to find similarly deviant-specific responses that cannot be explained by stimulus salience or SSA 19,21 . From our findings, the larval zebrafish fit into the latter category.…”
Section: Stimulus Specific Adaptation In Larval Zebrafishmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in rodents and pigeons successfully identified responses meeting these criteria 14,15,18 . However, efforts to identify an equivalent of MMN in songbirds and frogs failed to find similarly deviant-specific responses that cannot be explained by stimulus salience or SSA 19,21 . From our findings, the larval zebrafish fit into the latter category.…”
Section: Stimulus Specific Adaptation In Larval Zebrafishmentioning
confidence: 99%
“…An equivalent of the auditory MMN response is well established in rodents [13][14][15] . MMN-like responses are also present in the equivalent of the auditory cortex in macaques 16 , cats 17 , pigeons 18 and songbirds 19 , and there is preliminary evidence for auditory deviance responses in dogs 20 and frogs 21 , though interpretation of these findings are confounded by lack of role reversal for the expected and unexpected sounds. MMN can also be elicited in other sensory modalities 1 , and indeed visual MMN has been characterized in mice using calcium imaging 22 While the full complexity of the human MMN response may not be reflected in other species 14 , it stands to reason that the ability to detect changes in the sensory landscape would have arisen early in evolutionary time.…”
Section: Introductionmentioning
confidence: 99%